The Implementation of Song-Based Learning to Improve Vocabulary in English Learning - Putu Angellina Indah Iswari (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
English as an international language and the most widely used universally in the world, this condition requires education in Indonesia to implement English language learning as a provision for its human resources, but the facts on the ground show that many students at SMA Negeri 3 Singaraja are still not used to it. in English due to limited vocabulary. The aim of this research is to increase students' English vocabulary through English song-based learning. This research activity was carried out at SMA Negeri 3 Singaraja in class 10 with a sample of 38 students. The type of research used is qualitative with data collection techniques through interviews and observation. The research results explain that song-based learning in English learning can increase students' vocabulary to improve English language skills.